Peran Orang Tua dan Sekolah dalam Membentuk Generasi Rabbani - Rizki Pradika, Ayu Ratih; Yulfa, Rahmi (Jumat Keagamaan: Jurnal Pengabdian Masyarakat, 2025)
Rabbani education is crucial for shaping a generation with strong faith and morals. Rabbani education is expected to strengthen the character of the generation, enabling them to develop a personality formed through the internalization of various virtues, which serves as a foundation for righteous behavior in their lives. The implementation of Rabbani education for character building is inseparable from the role of parents in the family and teachers in schools. The purpose of this community service is to provide knowledge and understanding regarding the role of parents and schools in shaping the Rabbani generation, to offer additional insights into the factors contributing to children's character problems, and to offer understanding and solutions to parents and schools experiencing challenges with children's character development. This outreach used a visual communicative method based on PowerPoint presentations. The results obtained from this outreach were that this activity ran well thanks to the support of many parties, including the teachers and principal of PAUD SIMPATI 1, all parents/guardians of PAUD SIMPATI 1 students, and community leaders. It was deemed successful because the participants understood the lesson, as evidenced by the answers to several questions posed by the presenter to several participants.